Benefits of Using Pomace from Sea Buckthorn Fruit (Hippophaë rhamnoides L.) in the Production of Rye Bread for a Strategy of Sustainable Production and Consumption - Banach, Joanna Katarzyna; Majewska, Katarzyna; Piłat, Beata; Grzywińska-Rąpca, Małgorzata (Applied sciences, 2024)
The aim of the research was to optimize the addition of sea buckthorn pomace to rye bread for sustainable production and consumption. Profit analysis was used to evaluate the optimal impact of added pomace on bread quality. The effects of the management of the by-product (pomace) during the maceration of sea buckthorn fruit pulp were determined on the basis of process efficiency balance. The research materials included five baking variants of bread containing type 720 rye flour, differing in the level of pomace added (0, 5, 10, 15, and 20%). The bread was produced in laboratory conditions on rye sourdough using the three-phase method. The impact of pomace addition on the quality of baked goods was determined by assessing the content of nutritional and energy components, nutritional and building materials, and bioactive compounds. The results show that greater qualitative benefits, including health benefits, were obtained when rye bread was enriched with 15 and 20% pomace. These results have been confirmed by PROFIT analysis. The analysis of the efficiency balance of the sea buckthorn fruit pulp maceration process showed that it is more beneficial to subject these substrates to the processes of drying at 50 °C, separation (removal of seeds), and grinding than it is to use enzymatic maceration.